IDDF2019-ABS-0171 EUS-Guided radiofrequency ablation as adjunctive treatment for unresectable pancreatic cancer versus chemotherapy alone (ERAP). (June 2019) - Tiankanon, Kasenee; Kongkam, Pradermchai; Luangsukrerk, Thanawat; Sriuranpong, Virote; Nantavithya, Chonnipa; Jantarattana, Trirat; Canones, Arlyn; Angsuwatcharakon, Phonthep; Ridtitid, Wiriyaporn; Kullavanijaya, Pinit; Rerknimitr, Rungsun
Abstract : Background: Feasibility and safety of EUS-guided radiofrequency ablation (EUS-RFA) for unresectable pancreatic cancer (UPC) has been reported in only few small non-comparative studies. Aim: Compare radiological response and pain medication used between EUS-RFA plus chemotherapy versus chemotherapy (CMT) alone as primary treatment of UPC in prospective comparartive study. Methods: Patients with UPC with ECOG below 3 were recruited. Patients treated with EUS-RFA plus concurrent CMT were classified as group A. Control group was patients treated with CMT alone with matching clinical parameters (group B). All relevant parameters were compared (figure 1A ). Results: From July 2017 to August 2018, 28 patients (mean age 66.14?10years; M:F= 1:3) at King Chulalongkorn Memorial hospital were recruited. No statistical difference of baseline parameters (table 1 ). 34 EUS-RFA procedures were performed in 14 patients with median number of procedure 3 times (range 1–4 times), median total ablation time 270 seconds (range 90 - 962 seconds), and adverse event (AEs) rate 8.8% (3/34). Three AEs were post-procedure infection (length of stay (LOS) 7 days), bleeding puncture site (LOS 7 days) and mild pancreatitis (LOS 2 days). No delay of scheduled chemotherapy. 3 patients drop out due to disease progression in group A (n=11) and 1 patient loss to follow up in group B (n=13). Outcomes of both groups were compared (figure 1B ). Morphine equivalent analgesia dose reduction was significantly better in group A, 22.5 mg/day (range 0–60) versus 0 mg/day (-20 to 30) (p=0.003), respectively, as well as median percentage dosage reduction (50% (0 to 100) versus 0% (-100 to 42.9), p=0.001), respectively. No enlargement of mean maximal target lesion diameter (mm) in group A (before vs. after; 61.37?20.1 vs 64.25?22.0 (P = 0.099), but significant increase in group B (50.1?21.1 vs. 55.4?18 (p=0.017), respectively).No significant difference of 6-month survival rate. Conclusions: EUS-RFA plus concurrent CMT significantly reduce morphine dosage requirement than CMT in UPC. RFA additionally stabilized the tumor maximal target diameter whereas CMT failed.